Cartilage repair hydrogel material and preparation method thereof
The mechanics of existing cartilage repair hydrogel materials are solved by combining silk fibroin peptide, oxidized chondroitin sulfate and 3-aminophenylboronic acid, and adding modified T-ZIF-8 and Mg-MOF, as well as vitamin E derivatives. The problem of insufficient performance and cell affinity has achieved better cartilage repair results.
Patent Information
- Application Number
- CN202510035642.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The existing cartilage repair hydrogel materials have weak mechanical properties, poor cell affinity and weak bone regeneration ability.
Mg-MOF modified by compounding silk fibroitin sulfate/3-aminophenylboronic acid and adding 2,4-toluene diisocyanate modified T-ZIF-8 and SIKVAV peptide modified Mg-MOF, as well as vitamin E water-soluble derivatives D-α-tocopherol polyethylene glycol 1000 succinate is used to improve the mechanical properties, biological activity and antibacterial properties of the hydrogel.
It has achieved the improvement of the mechanical properties and biological activity of the hydrogel, enhanced its antibacterial and anti-inflammatory properties, promoted bone cell regeneration, and improved cartilage repair effect.
Smart Images

Figure CN119405890A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical materials, and specifically refers to a cartilage repair hydrogel material and a preparation method thereof. Background Art
[0002] Osteoarthritis is a degenerative joint disease and the main cause of chronic pain and mobility problems in the elderly. It begins with subtle, asymptomatic micro-injuries and inflammation. Patients with middle and late stage osteoarthritis usually present with severe joint pain, instability and dysfunction, and their quality of life is significantly impaired. Cartilage defect is the most serious stage of osteoarthritis, with irreversible damage to the cartilage and lesions in the subchondral bone, which are mainly caused by trauma, aging, osteoarthritis, etc. Since the subchondral bone cannot be penetrated, the stem cell population and bone marrow blood supply cannot be obtained, resulting in limited intrinsic repair capacity of the cartilage defect site. Conventional clinical treatments include microfracture surgery, autologous chondrocyte implantation, and matrix-induced autologous chondrocyte implantation. However, the implementation of these strategies is complex in itself, which can lead to damage to normal cartilage or subchondral bone, accompanied by graft degeneration and poor production of abnormal fibrocartilage. Without effective clinical treatment, osteochondral defects will gradually lead to joint pain, degenerative osteoarthritis, and even ultimately joint destruction. Therefore, an effective cartilage repair method is needed.
[0003] As a hydrophilic three-dimensional network structure, hydrogel is a good candidate material for cartilage repair and a research hotspot for the treatment of cartilage damage. The current existing technologies mainly have the problems of weak mechanical properties of hydrogels, poor cell affinity and weak bone regeneration ability. Summary of the invention
[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a cartilage repair hydrogel material and a preparation method thereof. In order to solve the problems of weak mechanical properties, poor cell affinity and weak bone regeneration ability of the hydrogel, the present invention proposes to improve the mechanical properties and biological activity of the hydrogel by compounding silk fibroin peptide / oxidized chondroitin sulfate / 3-aminophenylboronic acid, and at the same time add 2,4-toluene diisocyanate-modified T-ZIF-8 and SIKVAV peptide-modified Mg-MOF to improve the antibacterial property of the hydrogel, increase the affinity of the hydrogel with bone cells, and further promote the regeneration of bone cells, and add a water-soluble derivative of vitamin E D-α-tocopherol polyethylene glycol 1000 succinate to improve its anti-inflammatory and antioxidant properties.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows: The present invention proposes a method for preparing a cartilage repair hydrogel material, characterized in that the preparation method comprises the following steps:
[0006] S1. Slice the silkworm cocoon and crush it through a 100-mesh sieve, add deionized water and mix, extract at 90-100°C for 8-10h, extract 2-3 times, combine the extracts and filter to obtain a filtrate, concentrate the filtrate by rotary evaporation at 50-60°C to 30-40% of the volume of the filtrate to obtain a concentrate, add trypsin, perform enzymolysis at 32-36°C for 3-5h to obtain an enzymolysis solution, place the enzymolysis solution in an autoclave, inactivate the enzyme in a boiling water bath for 12-16min, cool to room temperature, centrifuge at 5000-7000rpm for 8-10min, take the supernatant, pass the supernatant through a 0.22μm filter membrane, and irradiate with ultraviolet light for 20-30min to obtain a silk fibroin peptide solution for standby use;
[0007] S2, dissolving the oxidized chondroitin sulfate in a phosphate buffer solution with a pH of 7.5 and a concentration of 0.01 mol / L for 1-2 hours, adding the silk fibroin peptide solution under a nitrogen atmosphere, heating to 65-75° C., stirring evenly, obtaining the silk fibroin peptide / oxidized chondroitin sulfate, and setting aside;
[0008] S3, dissolving 3-aminophenylboronic acid in dimethyl sulfoxide to obtain a 3-aminophenylboronic acid solution; adding the 3-aminophenylboronic acid solution to the silk fibroin peptide / oxidized chondroitin sulfate obtained in S2 under an argon atmosphere, adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide, heating to 70-80° C., stirring at 6000-8000 rpm for 20-30 min, obtaining silk fibroin peptide / oxidized chondroitin sulfate / 3-aminophenylboronic acid, and setting aside;
[0009] S4, dissolving T-ZIF-8 in a mixed solvent of dichloromethane and methanol in a volume ratio of 4:1, adding 2,4-toluene diisocyanate, stirring at 3000-5000 rpm for 2-3 hours, filtering, taking the precipitate, and drying at 80° C. for 5-6 hours to obtain 2,4-toluene diisocyanate-modified T-ZIF-8, which is set aside;
[0010] S5, dissolving Mg-MOF in deionized water, adding SIKVAV peptide, magnetically stirring at 1000-2000 rpm for 10-14 h, centrifuging at 10000-15000 rpm for 8-14 min, taking the precipitate, washing it with deionized water for 2-3 times, and vacuum drying to obtain SIKVAV peptide-modified Mg-MOF for later use;
[0011] S6. Add D-α-tocopherol polyethylene glycol 1000 succinate, 2,4-toluene diisocyanate-modified T-ZIF-8 and SIKVAV peptide-modified Mg-MOF to the silk fibroin peptide / oxidized chondroitin sulfate / 3-aminophenylboronic acid obtained in S3, cross-link under ultraviolet light to obtain a cartilage repair hydrogel material.
[0012] Preferably, in S1, the material-liquid ratio of the silkworm cocoons to the ionized water is 1 g:16-20 mL;
[0013] Preferably, in S1, the amount of trypsin added is 0.4-0.8% of the mass of the silkworm cocoons;
[0014] Preferably, in S2, the amount of the oxidized chondroitin sulfate added to the phosphate buffered saline solution is 0.3-0.5 g / mL;
[0015] Preferably, in S2, the mass volume ratio of the oxidized sulfated cartilage and the silk fibroin peptide solution is 1-2 g:10-12 mL;
[0016] Preferably, in S2, the method for preparing oxidized chondroitin sulfate specifically comprises the following steps:
[0017] Dispersing chondroitin sulfate in anhydrous ethanol to obtain a chondroitin sulfate dispersion, dissolving sodium periodate in distilled water to obtain a sodium periodate aqueous solution, mixing the chondroitin sulfate dispersion and the sodium periodate aqueous solution, reacting for 3-5 hours in an ice bath in the dark, centrifuging at 2000-3000 rpm for 20-30 minutes, dialyzing for 68-74 hours using a dialysis bag with a molecular weight cutoff of 5 kD, and freeze-drying the dialyzate to obtain oxidized chondroitin sulfate;
[0018] Preferably, the mass volume ratio of the chondroitin sulfate to anhydrous ethanol is 10-15g:50-60mL;
[0019] Preferably, the mass volume ratio of the sodium periodate to distilled water is 5-6 g:30-50 mL;
[0020] Chondroitin sulfate is a natural polysaccharide with good cell affinity. Chondroitin sulfate can combine with silk fibroin peptide components to maintain the healthy structure of the cartilage matrix, enhance the compression resistance and elasticity of the cartilage, and help restore the function of damaged cartilage.
[0021] Preferably, in S3, the mass volume ratio of the 3-aminophenylboronic acid to dimethyl sulfoxide is 8-10 g:40-50 mL;
[0022] Preferably, in S3, the volume mass ratio of the 3-aminophenylboric acid solution, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide is 10-20 mL: 0.1-0.2 g: 0.08-0.12 g;
[0023] Preferably, in S4, the preparation method of T-ZIF-8 specifically comprises the following steps:
[0024] Dissolve zinc nitrate hexahydrate in methanol to obtain a zinc nitrate solution, and dissolve 2-methylimidazole in methanol to obtain a 2-methylimidazole solution; disperse the zinc nitrate solution in the 2-methylimidazole solution, stir for 1-2 minutes, centrifuge at 10000-15000 rpm for 8-12 minutes, take the precipitate, wash it with methanol and deionized water 2-3 times, and vacuum dry it to obtain ZIF-8; heat treat ZIF-8 in an oxygen atmosphere at 200° C. for 4-5 hours to obtain T-ZIF-8;
[0025] Preferably, the amount of zinc nitrate hexahydrate dissolved in methanol is 28-32 mg / mL;
[0026] Preferably, the amount of 2-methylimidazole added to methanol is 30-35 mg / mL;
[0027] Preferably, in S4, the amount of T-ZIF-8 added to the mixed solvent of dichloromethane and methanol is 10-12 mg / mL;
[0028] Preferably, in S4, the mass volume ratio of the T-ZIF-8 to 2,4-toluene diisocyanate is 100-120 mg:1 mL.
[0029] Preferably, in S5, the method for preparing Mg-MOF specifically comprises the following steps:
[0030] 2,5-dihydroxyterephthalic acid, Mg(NO3)2·6H2O and polyvinylpyrrolidone are added to N,N-dimethylacetamide, dispersed by ultrasonication, and ammonia water is added. The mixture is heated at 100-120°C for 8-10 hours, centrifuged at 8000-10000 rpm for 6-10 minutes, and the precipitate is taken, washed with acetone and deionized water for 2-3 times, and dried in vacuo to obtain Mg-MOF.
[0031] Preferably, the mass ratio of 2,5-dihydroxyterephthalic acid, Mg(NO3)2·6H2O and polyvinylpyrrolidone is 15-17 mg:28-30 mg:10-12 mg;
[0032] Preferably, the amount of polyvinyl pyrrolidone added to N,N-dimethylacetamide is 1.5-1.7 mg / mL;
[0033] Preferably, the volume ratio of the aqueous ammonia to N,N-dimethylacetamide is 1 mL:100-120 mL;
[0034] Preferably, in S5, the amount of Mg-MOF added to deionized water is 1-1.4 mg / mL;
[0035] Preferably, in S5, the mass ratio of the Mg-MOF to the SIKVAV peptide is 100 mg:1-1.2 mg;
[0036] Preferably, in S6, the volume mass ratio of the silk fibroin peptide / oxidized chondroitin sulfate / 3-aminophenylboronic acid, D-α-tocopheryl polyethylene glycol 1000 succinate, WYRGRL-modified ZIF-8 and SIKVAV-modified Mg-MOF is 100 mL: 0.01-0.05 g: 0.5-0.7 g: 0.1-0.2 g.
[0037] The present invention provides a cartilage repair hydrogel material prepared by the above preparation method.
[0038] The beneficial effects achieved by the present invention are as follows:
[0039] The present invention uses silk fibroin peptide, oxidized chondroitin sulfate, and 3-aminophenylboronic acid as main materials, and simultaneously adds 2,4-toluene diisocyanate-modified T-ZIF-8 and SIKVAV peptide-modified Mg-MOF and vitamin E water-soluble derivative D-α-tocopherol polyethylene glycol 1000 succinate. The components act synergistically to obtain a hydrogel material for cartilage repair that has good mechanical properties and cell affinity, is antibacterial and anti-inflammatory, and promotes bone cell regeneration.
[0040] 1. Silk fibroin peptide has good structural stability and biocompatibility. It exists in hydrogel materials as a scaffold support material to provide support for the growth of chondrocytes. Compared with silk fibroin, silk fibroin peptide contains specific bioactive peptide segments, which can induce chondrocytes to differentiate into chondrocytes and help chondrocytes better express cartilage-specific genes. Because the peptide segments are smaller, they can more easily penetrate into the cells and bind to receptors on the surface of chondrocytes, promoting the adhesion and proliferation of chondrocytes, which is beneficial to the growth and reproduction of chondrocytes during the repair process and accelerating the formation and repair process of cartilage tissue;
[0041] 2. After being modified by aldehyde group, chondroitin sulfate still retains functional carboxyl groups and sulfate groups. The carboxyl group can form a stable chemical bond with bioactive substances such as growth factors and drugs. The carboxyl group in oxidized chondroitin sulfate reacts with the amino group in the cartilage matrix to undergo an amidation reaction, thereby achieving adhesion of the hydrogel to the damaged cartilage matrix and improving the stability of the hydrogel material. The sulfate group makes the oxidized chondroitin sulfate present a negative charge, and the negative charge density on the surface of the hydrogel increases, so that the isoelectric point of the hydrogel material moves to a lower pH value, and more water molecules can be attracted through hydrogen bond interactions, which is manifested as an increase in hydrophilicity, thereby improving its stability in aqueous solution. The increase in hydrophilicity leads to an increase in the viscosity of the hydrogel, which is beneficial to improving its gel strength.
[0042] 3. By adding 3-aminophenylboronic acid, on the one hand, the aldehyde group of oxidized chondroitin sulfate and the amino group of 3-aminophenylboronic acid undergo a Schiff base reaction, which is beneficial to improving the stability of the hydrogel material with a three-dimensional complex cross-linked structure and increasing its porosity, so that the water-soluble derivative of vitamin E D-α-tocopherol polyethylene glycol 1000 succinate can stably adhere to the porous surface through the complex pores, thereby improving its anti-inflammatory and antioxidant properties; on the other hand, the boric acid group is introduced to form a borate ester bond with the hydroxyl group on the metal surface. The introduction of the borate ester bond creates an adhesion group for the surface of the hydrogel material, which can provide more binding sites, increase the binding opportunities between bone cells and the surface of the hydrogel material, and achieve the technical effect of promoting cell adhesion;
[0043] 4. T-ZIF-8 was obtained by heat treating ZIF-8 at high temperature in an oxygen atmosphere, so that more hydroxyl groups were exposed on its surface. On the one hand, hydroxyl groups can improve the hydrophilicity of the hydrogel, promote cell attachment and proliferation, thereby improving the compatibility of the hydrogel material with biological tissues, reducing the rejection of metal materials by tissues, and helping to reduce inflammatory reactions and promote wound healing; on the other hand, the surface of T-ZIF-8 after high temperature heat treatment has a negative charge, which can react with positively charged Ca in physiological fluids. 2+ The combination forms amorphous calcium phosphate, which is beneficial to further improve the cartilage repair ability of the hydrogel material; adding 2,4-toluene diisocyanate, a stable ester bond is formed between the hydroxyl group on the surface of T-ZIF-8 and the carbon-oxygen double bond of 2,4-toluene diisocyanate, and the 2,4-toluene diisocyanate-modified T-ZIF-8 selectively migrates to the tendon, releasing zinc ions, improving its antibacterial and antimicrobial properties, promoting collagen secretion, and promoting tendon repair; at the same time, the SIKVAV peptide-modified Mg-MOF migrates to the cartilage, releasing magnesium ions, inducing cell differentiation, and promoting cartilage regeneration. The two work synergistically to improve the cell affinity of the hydrogel material and promote bone cell regeneration. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 The test results of tensile strength and elongation at break of the hydrogel materials prepared in Examples 1-3 and Comparative Examples 1-4 of the present invention are shown in FIG.
[0045] Figure 2 The test results of compressive strength and elastic modulus of the hydrogel materials prepared in Examples 1-3 and Comparative Examples 1-4 of the present invention are shown in FIG.
[0046] Figure 3 The porosity test results of the hydrogel materials prepared in Examples 1-3 and Comparative Examples 1-4 of the present invention are shown in FIG.
[0047] Figure 4 The results of the cell adhesion test of the hydrogel materials prepared in Examples 1-3 and Comparative Examples 1-4 of the present invention are shown;
[0048] Figure 5 The antibacterial performance test results of the hydrogel materials prepared in Examples 1-3 and Comparative Examples 1-4 of the present invention are shown in FIG.
[0049] Figure 6 This is a SEM image of the hydrogel material prepared in Example 1 of the present invention;
[0050] Figure 7 This is the SEM image of T-ZIF-8 modified with 2,4-toluene diisocyanate prepared in Example 1 of the present invention.
[0051] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION
[0052] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0053] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.
[0054] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.
[0055] Example 1
[0056] A method for preparing a cartilage repair hydrogel material comprises the following steps:
[0057] S1. Slice 10g of silkworm cocoons and crush them through a 100-mesh sieve, add 160mL of deionized water and mix, extract at 90°C for 8h, extract twice, combine the extracts and filter to obtain a filtrate, concentrate the filtrate by rotary evaporation at 50°C to 30% of the filtrate volume to obtain a concentrate, add 0.04g of trypsin, perform enzymolysis at 32°C for 3h to obtain an enzymolysis solution, place the enzymolysis solution in an autoclave, inactivate the enzyme in a boiling water bath for 12min, cool to room temperature, centrifuge at 5000rpm for 8min, take the supernatant, pass the supernatant through a 0.22μm filter membrane, and irradiate with ultraviolet light for 20min to obtain a silk fibroin peptide solution for standby use;
[0058] S2, dissolving 10 g of oxidized chondroitin sulfate in 33.3 mL of phosphate buffered saline with a pH of 7.5 and a concentration of 0.01 mol / L for 1 h, adding 100 mL of silk fibroin peptide solution under a nitrogen atmosphere, heating to 65° C., stirring evenly, obtaining silk fibroin peptide / oxidized chondroitin sulfate, and setting aside;
[0059] S3, dissolving 8g 3-aminophenylboronic acid in 40mL dimethyl sulfoxide to obtain a 3-aminophenylboronic acid solution; adding the 3-aminophenylboronic acid solution to the silk fibroin peptide / oxidized chondroitin sulfate obtained in S2 under an argon atmosphere, adding 0.48g 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 0.384g N-hydroxysuccinimide, heating to 70°C, stirring at 6000rpm for 20min, obtaining silk fibroin peptide / oxidized chondroitin sulfate / 3-aminophenylboronic acid, and setting aside;
[0060] S4, dissolving 1 g of T-ZIF-8 in 100 mL of a mixed solvent of dichloromethane and methanol in a volume ratio of 4:1, adding 10 mL of 2,4-toluene diisocyanate, stirring at 3000 rpm for 2 h, filtering, taking the precipitate, and drying at 80 ° C for 5 h to obtain 2,4-toluene diisocyanate-modified T-ZIF-8, which is set aside;
[0061] S5, dissolving 0.5 g Mg-MOF in 500 mL deionized water, adding 5 mg SIKVAV peptide, magnetically stirring at 1000 rpm for 10 h, centrifuging at 10000 rpm for 8 min, taking the precipitate, washing it twice with deionized water, and vacuum drying to obtain SIKVAV peptide-modified Mg-MOF for later use;
[0062] S6. Add 0.01 g of D-α-tocopherol polyethylene glycol 1000 succinate, 0.5 g of 2,4-toluene diisocyanate-modified T-ZIF-8 and 0.1 g of SIKVAV peptide-modified Mg-MOF to 100 mL of the silk fibroin peptide / oxidized chondroitin sulfate / 3-aminophenylboronic acid obtained, and cross-link under ultraviolet light to obtain a cartilage repair hydrogel material.
[0063] The surface morphology of the hydrogel material prepared in Example 1 was observed using a scanning electron microscope. Figure 6 The SEM image of the hydrogel material prepared in Example 1 of the present invention; the surface morphology of the 2,4-toluene diisocyanate-modified T-ZIF-8 prepared in Example 1 was observed using a scanning electron microscope. Figure 7 This is the SEM image of T-ZIF-8 modified with 2,4-toluene diisocyanate prepared in Example 1 of the present invention.
[0064] The preparation method of oxidized chondroitin sulfate specifically comprises the following steps:
[0065] Disperse 10 g of chondroitin sulfate in 50 mL of anhydrous ethanol to obtain a chondroitin sulfate dispersion, dissolve 5 g of sodium periodate in 30 mL of distilled water to obtain a sodium periodate aqueous solution, mix the chondroitin sulfate dispersion and the sodium periodate aqueous solution, react for 3 h in an ice bath in the dark, centrifuge at 2000 rpm for 20 min, dialyze for 68 h using a dialysis bag with a molecular weight cutoff of 5 kD, and lyophilize the dialysate to obtain oxidized chondroitin sulfate.
[0066] The preparation method of T-ZIF-8 specifically comprises the following steps:
[0067] 1 g of zinc nitrate hexahydrate was dissolved in 35.7 mL of methanol to obtain a zinc nitrate solution, and 0.5 g of 2-methylimidazole was dissolved in 16.6 mL of methanol to obtain a 2-methylimidazole solution; the zinc nitrate solution was dispersed in the 2-methylimidazole solution, stirred for 1 min, centrifuged at 10000 rpm for 8 min, the precipitate was taken, washed twice with methanol and deionized water, and vacuum dried to obtain ZIF-8; ZIF-8 was heat treated in an oxygen atmosphere at 200°C for 4 h to obtain T-ZIF-8.
[0068] The preparation method of Mg-MOF specifically comprises the following steps:
[0069] 150 mg of 2,5-dihydroxyterephthalic acid, 280 mg of Mg(NO3)2·6H2O and 100 mg of polyvinylpyrrolidone were added to 66.7 mL of N,N-dimethylacetamide, ultrasonically dispersed, 0.6 mL of ammonia water was added, heated at 100°C for 8 h, centrifuged at 8000 rpm for 6 min, the precipitate was taken, washed twice with acetone and deionized water, and vacuum dried to obtain Mg-MOF.
[0070] Example 2
[0071] A method for preparing a cartilage repair hydrogel material comprises the following steps:
[0072] S1. Slice 10g of silkworm cocoons and crush them through a 100-mesh sieve, add 180mL of deionized water and mix, extract at 95°C for 9h, extract twice, combine the extracts and filter to obtain a filtrate, concentrate the filtrate by rotary evaporation at 55°C to 35% of the filtrate volume to obtain a concentrate, add 0.06g of trypsin, perform enzymolysis at 34°C for 4h to obtain an enzymolysis solution, place the enzymolysis solution in an autoclave, inactivate the enzyme in a boiling water bath for 14min, cool to room temperature, centrifuge at 6000rpm for 9min, take the supernatant, pass the supernatant through a 0.22μm filter membrane, and irradiate with ultraviolet light for 25min to obtain a silk fibroin peptide solution for standby use;
[0073] S2, dissolving 15 g of oxidized chondroitin sulfate in 37.5 mL of phosphate buffered saline with a pH of 7.5 and a concentration of 0.01 mol / L for 1.5 h, adding 110 mL of silk fibroin peptide solution under a nitrogen atmosphere, heating to 70° C., stirring evenly, obtaining silk fibroin peptide / oxidized chondroitin sulfate, and setting aside;
[0074] S3, dissolving 9g 3-aminophenylboronic acid in 45mL dimethyl sulfoxide to obtain a 3-aminophenylboronic acid solution; adding the 3-aminophenylboronic acid solution to the silk fibroin peptide / oxidized chondroitin sulfate obtained in S2 under an argon atmosphere, adding 0.54g 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 0.36g N-hydroxysuccinimide, heating to 75°C, stirring at 7000rpm for 25min, obtaining silk fibroin peptide / oxidized chondroitin sulfate / 3-aminophenylboronic acid, and setting aside;
[0075] S4, dissolving 1.1 g of T-ZIF-8 in 100 mL of a mixed solvent of dichloromethane and methanol in a volume ratio of 4:1, adding 10 mL of 2,4-toluene diisocyanate, stirring at 4000 rpm for 2.5 h, filtering, taking the precipitate, and drying at 80° C. for 5.5 h to obtain 2,4-toluene diisocyanate-modified T-ZIF-8, which is set aside;
[0076] S5, dissolving 0.6 g of Mg-MOF in 500 mL of deionized water, adding 6.6 mg of SIKVAV peptide, magnetically stirring at 1000 rpm for 12 h, centrifuging at 12500 rpm for 12 min, taking the precipitate, washing it twice with deionized water, and vacuum drying to obtain SIKVAV peptide-modified Mg-MOF for later use;
[0077] S6. Add 0.03 g of D-α-tocopherol polyethylene glycol 1000 succinate, 0.6 g of 2,4-toluene diisocyanate-modified T-ZIF-8 and 0.15 g of SIKVAV peptide-modified Mg-MOF to 100 mL of the silk fibroin peptide / oxidized chondroitin sulfate / 3-aminophenylboronic acid obtained, and cross-link under ultraviolet light to obtain a cartilage repair hydrogel material.
[0078] The preparation methods of oxidized chondroitin sulfate, T-ZIF-8 and Mg-MOF can be referred to Example 1.
[0079] Example 3
[0080] S1. Slice 10 g of silkworm cocoons and grind them through a 100-mesh sieve, add 200 mL of deionized water and mix, extract at 10°C for 10 h, extract 3 times, combine the extracts and filter to obtain a filtrate, concentrate the filtrate by rotary evaporation at 60°C to 40% of the filtrate volume to obtain a concentrate, add 0.08 g of trypsin, perform enzymolysis at 36°C for 5 h to obtain an enzymolysis solution, place the enzymolysis solution in an autoclave, inactivate the enzyme in a boiling water bath for 16 min, cool to room temperature, centrifuge at 7000 rpm for 10 min, take the supernatant, pass the supernatant through a 0.22 μm filter membrane, and irradiate with ultraviolet light for 30 min to obtain a silk fibroin peptide solution for standby use;
[0081] S2, dissolving 20 g of oxidized chondroitin sulfate in 40 mL of phosphate buffered saline with a pH of 7.5 and a concentration of 0.01 mol / L for 2 h, adding 120 mL of silk fibroin peptide solution under a nitrogen atmosphere, heating to 75° C., stirring evenly, obtaining silk fibroin peptide / oxidized chondroitin sulfate, and setting aside;
[0082] S3, dissolving 10g 3-aminophenylboronic acid in 50mL dimethyl sulfoxide to obtain a 3-aminophenylboronic acid solution; adding the 3-aminophenylboronic acid solution to the silk fibroin peptide / oxidized chondroitin sulfate obtained in S2 under an argon atmosphere, adding 0.6g 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 0.36g N-hydroxysuccinimide, heating to 80°C, stirring at 8000rpm for 30min, obtaining silk fibroin peptide / oxidized chondroitin sulfate / 3-aminophenylboronic acid, and setting aside;
[0083] S4, dissolving 1.2 g of T-ZIF-8 in 100 mL of a mixed solvent of dichloromethane and methanol in a volume ratio of 4:1, adding 10 mL of 2,4-toluene diisocyanate, stirring at 5000 rpm for 3 h, filtering, taking the precipitate, and drying at 80° C. for 6 h to obtain 2,4-toluene diisocyanate-modified T-ZIF-8, which is set aside;
[0084] S5, dissolving 0.7 g Mg-MOF in 500 mL deionized water, adding 8.4 mg SIKVAV peptide, magnetically stirring at 1000 rpm for 14 h, centrifuging at 15000 rpm for 14 min, taking the precipitate, washing it with deionized water for 3 times, and vacuum drying to obtain SIKVAV peptide-modified Mg-MOF for later use;
[0085] S6. Add 0.05 g of D-α-tocopherol polyethylene glycol 1000 succinate, 0.7 g of 2,4-toluene diisocyanate-modified T-ZIF-8 and 0.2 g of SIKVAV peptide-modified Mg-MOF to 100 mL of the silk fibroin peptide / oxidized chondroitin sulfate / 3-aminophenylboronic acid obtained, and cross-link under ultraviolet light to obtain a cartilage repair hydrogel material.
[0086] The preparation methods of oxidized chondroitin sulfate, T-ZIF-8 and Mg-MOF can be referred to Example 1.
[0087] Comparative Example 1
[0088] This comparative example provides a cartilage repair hydrogel material and a preparation method thereof, which is different from Example 1 only in that chondroitin sulfate is not subjected to oxidation treatment, and the remaining components and component contents are the same as those in Example 1.
[0089] Comparative Example 2
[0090] This comparative example provides a cartilage repair hydrogel material and a preparation method thereof, which differs from Example 1 only in that 3-aminophenylboronic acid is not included, and the remaining components and component contents are the same as those in Example 1.
[0091] Comparative Example 3
[0092] This comparative example provides a cartilage repair hydrogel material and a preparation method thereof, which is different from Example 1 only in that the surface of ZIF-8 is not subjected to high-temperature heat treatment and 2,4-toluene diisocyanate is not grafted, and the remaining components and component contents are the same as those in Example 1.
[0093] Comparative Example 4
[0094] This comparative example provides a cartilage repair hydrogel material and a preparation method thereof, which is different from Example 1 only in that Mg-MOF modified with SIKVAV peptide is not included, and the remaining components and component contents are the same as those in Example 1.
[0095] Performance testing and result analysis
[0096] 1. Mechanical properties test of hydrogel materials
[0097] Test method: The hydrogel materials prepared in Examples 1-3 and Comparative Examples 1-4 were extruded into sample strips with a diameter of 20 mm × 10 mm × 100 μm (length × width × thickness). After the samples were fully formed, they were placed in a stretching device for a stretching test at a stretching rate of 1.0 mm / min and a stretching force of 50 N. The samples were stretched until they broke, and the tensile strength and elongation at break of each group of hydrogel materials were calculated. After the customer implant materials prepared in Examples 1-3 and Comparative Examples 1-4 were made into sample strips, they were placed on the platform of a universal mechanical testing machine and compressed along the long axis of the sample strip at a speed of 0.5 mm / min. The compression was stopped when the deformation was 10%, and the compressive strength and elastic modulus were calculated.
[0098] Result analysis: Figure 1 The graphs are test results of tensile strength and elongation at break of the hydrogel materials prepared in Examples 1-3 and Comparative Examples 1-4 of the present invention. Figure 2 The test results of compressive strength and elastic modulus of the hydrogel materials prepared in Examples 1-3 and Comparative Examples 1-4 of the present invention are shown in the figure. As shown in the figure, the tensile properties and compressive properties of the hydrogel materials prepared in Comparative Examples 1-4 are significantly lower than those of the hydrogel materials prepared in Examples 1-3. In Comparative Example 1, the chondroitin sulfate is not oxidized, so the chondroitin sulfate has no aldehyde group and cannot react with 3-aminophenylboronic acid to form a Schiff base reaction. Comparative Example 2 does not include 3-aminophenylboronic acid, and the metal surface hydroxyl group cannot form a borate ester bond with the boronic acid group, and cannot react with the oxidized chondroitin sulfate to form a Schiff base reaction, thereby reducing the degree of cross-linking between the components. Therefore, the mechanical properties of the hydrogel materials prepared in Comparative Examples 1 and 2 will decrease; Comparative Example 4 does not include any Mg-MOF, lacks the support of the metal material, and the mechanical properties will be reduced.
[0099] 2. Porosity test of hydrogel materials
[0100] Test method: The dry hydrogel materials prepared in Examples 1-3 and Comparative Examples 1-4 were recorded with a mass m, immersed in anhydrous ethanol, and the pores of the cartilage repair hydrogel material were completely filled with ethanol. The cartilage repair hydrogel material was then transferred to a measuring cylinder containing ethanol with a known initial volume and weight v1 and m1, respectively. The volumes and weights of the hydrogel material and ethanol in the measuring cylinder were recorded as v2 and m2, respectively. The porosity was calculated according to the following formula:
[0101] ;
[0102] Result analysis: Figure 3The porosity test results of the hydrogel materials prepared in Examples 1-3 of the present invention and Comparative Examples 1-4 are shown in the figure. As shown in the figure, the porosities of the hydrogel materials prepared in Examples 1-3 are 94.2%, 93.6% and 92.8%, respectively, which are significantly higher than the porosity of the hydrogel materials prepared in Comparative Examples 1-4. This is because a Schiff base reaction occurs between the aldehyde groups of oxidized chondroitin sulfate and the amino groups of 3-aminophenylboronic acid in the hydrogel materials prepared in Examples 1-3, thereby improving the stability of the hydrogel material with a three-dimensional complex cross-linked structure and increasing its porosity. A stable ester bond is formed between the hydroxyl groups on the surface of T-ZIF-8 and the carbon-oxygen double bonds of 2,4-toluene diisocyanate. Mg-MOF is modified with SIKVAV peptide to increase the surface size of Mg-MOF. The components act synergistically to obtain a highly stable hydrogel material with a porous cross-linked structure.
[0103] 3. Test of cell adhesion performance of hydrogel materials:
[0104] Test method: MC3T3-E1 mouse embryonic osteoblasts were selected as experimental cells, and DMEM medium containing 10% fetal bovine serum and 1% penicillin / streptomycin was used for culture. The osteoblasts were co-cultured on the surface of the hydrogel materials prepared in Examples 1-3 and Comparative Examples 1-4 in a 96-well plate for 24 hours, and then taken out and repeatedly washed with PBS buffer to remove cells that failed to attach successfully; 30 μL CCK-8 solution and 300 μL culture medium were added to each well under light-proof conditions, and culture was continued for 12 hours, and then 100 μL of the supernatant was aspirated and the absorbance value (OD) was measured with an ELISA reader, and the wavelength was set to 450 nm. The cell adhesion rate was calculated according to the following formula: Adhesion rate = (number of adherent cells / total number of cells) × 100%.
[0105] Result analysis: Figure 4The results of the cell adhesion performance test of the hydrogel materials prepared in Examples 1-3 and Comparative Examples 1-4 of the present invention are shown in the figure. As shown in the figure, the cell adhesion rates of the hydrogel materials prepared in Examples 1-3 are 31.8%, 32.5% and 33.6, respectively, while the cell adhesion rates of the hydrogel materials prepared in Comparative Examples 1-4 are only 22.7%, 24.3%, 27.1% and 25.2%, respectively. This is because the carboxyl groups in the oxidized chondroitin sulfate in the hydrogel materials prepared in Examples 1-3 react with the amino groups in the cartilage matrix to achieve the adhesion of the hydrogel to the damaged cartilage matrix and improve the stability of the hydrogel material. Boric acid groups are introduced by adding 3-aminophenylboronic acid to form borate ester bonds with the hydroxyl groups on the metal surface. The introduction of borate ester bonds creates adhesion groups on the surface of the hydrogel material, can provide more binding sites, increase the binding opportunities of bone cells to the surface of the hydrogel material, and achieve the technical effect of promoting cell adhesion. The surface of T-ZIF-8 obtained after high-temperature heat treatment of ZIF-8 is negatively charged, which can react with positively charged Ca in physiological fluids. 2+ The combination forms amorphous calcium phosphate, thereby improving the adhesion of the hydrogel material to bone cells, which is beneficial to further improve the cartilage repair ability of the hydrogel material.
[0106] 4. Antibacterial performance test of hydrogel materials:
[0107] Test method: The hydrogel materials prepared in Examples 1-3 and Comparative Examples 1-4 were placed in corresponding groups on a 48-well plate, with 3 samples in each group, and the concentration of Staphylococcus aureus liquid was adjusted to 10 6 CFU / mL, then add 300μL of Staphylococcus aureus liquid to each well, and cover it with a sterile PE film, flatten it so that the liquid evenly covers the sample surface. To prevent the liquid on the sample surface from volatilizing, add sterile water to the gaps around the 48-well plate, and the humidity is 95%. After incubating in a 37℃ electric constant temperature incubator for 6 hours, wash the bacteria on the sample surface with PBS solution and collect them, draw 100μL of the eluate and drop it on the nutrient agar medium plate, spread it evenly, invert it at 37℃ and incubate it for 24 hours, take out the plate, take pictures and count the number of live colonies in the fully automatic colony analyzer, and detect its antibacterial properties.
[0108] Result analysis: Figure 5The results of the antibacterial property test of the hydrogel materials prepared in Examples 1-3 and Comparative Examples 1-4 of the present invention are shown in the figure. As shown in the figure, the antibacterial rates of the hydrogel materials prepared in Examples 1-3 are 86.1%, 85.4% and 87.2%, respectively, while the antibacterial rates of the hydrogel materials prepared in Comparative Examples 1-4 are only 82.4%, 83.6%, 67.5% and 81.3%, respectively. The borate bond and the oxidized chondroitin sulfate have antibacterial properties, so the antibacterial rates of Comparative Examples 1-2 and 4 will decrease; in the hydrogel material prepared in Comparative Example 3, ZIF-8 is not subjected to high-temperature heat treatment, so no more hydroxyl groups are exposed on the surface, and a stable ester bond cannot be formed with the carbon-oxygen double bond of 2,4-toluene diisocyanate, thereby reducing the antibacterial rate, indicating that grafting 2,4-toluene diisocyanate on the surface of ZIF-8 after high-temperature heat treatment to release zinc ions can improve the antibacterial and antibacterial properties of the hydrogel material.
[0109] Animal cartilage repair experiment
[0110] Establishment of cartilage defect model: 80 SD rats weighing 200-250g were selected. The rats were fasted for 12h and fasted for 3h before surgery, and randomly divided into 7 groups, each with 10 rats, namely, Example 1-3 group, Comparative Example 1-4 group and blank control group; the rats were anesthetized by intraperitoneal injection of 10% chloral hydrate solution (800μL / rat), the right knee joint of the rat was selected as the experimental site, the right knee joint was completely depilated with a disposable skin preparation blade, and the exposed skin was disinfected with a sterile medical cotton swab dipped in iodine solution, and then the skin was wiped with 75% medical alcohol for deiodination, and a cylindrical full-thickness cartilage defect with a diameter of 2mm and a depth of 3mm was made at the right knee joint of the rat using sterile surgical scissors, the depth of which reached the subchondral bone, and after removing the blood clot in the defect, the Example 1-3 group and the Comparative Example 1-4 group were implanted with the Example 1 respectively. -3. The hydrogel material prepared in Comparative Examples 1-4 was illuminated at the defect for 20 seconds using a handheld ultraviolet curing light to completely crosslink the precursor solution to form a hydrogel scaffold. No material was implanted in the blank control group. After the treatment, the ligaments and skin were sutured in turn, the wound was disinfected with iodine solution, and penicillin G sodium antibiotic solution (120 mg / mouse) was injected. The animals were observed at all times until they were put back into the cage after waking up from anesthesia, and were raised separately in separate cages. Penicillin G sodium antibiotic solution was continuously injected for 2 days at the same dose. The affected limb was not fixed and immobilized, and the animals were allowed to move normally. After surgery, they were fed with standard pellet feed and had free access to water. The conditions were observed daily. If there were any abnormalities, they were treated in time. CT examinations were performed after 12 weeks to observe the repair of the osteochondrium, and the International Cartilage Repair Society (ICRS) scoring criteria were used for scoring. The specific scoring criteria are shown in Table 1:
[0111] Table 1 ICRS scoring criteria
[0112]
[0113] The results of the animal cartilage repair experiment are shown in Table 2:
[0114] Table 2 Animal cartilage repair experimental results
[0115]
[0116] Result analysis: From the results of the animal cartilage repair experiment in Table 2, it can be seen that the hydrogel materials prepared in Examples 1-3 of the present invention repaired the defective tissue in the same manner as the surrounding normal cartilage, the boundary integration was no obvious boundary, the surface of the general structure was smooth, and the overall repair evaluation score reached 11.2-11.4 points, reaching the I-level repair degree, and the normal structure was completely restored; this shows that the silk protein peptide is more likely to penetrate into the cells, bind to the receptors on the surface of the chondrocytes, promote the adhesion and proliferation of the chondrocytes, and is beneficial to the growth and reproduction of the chondrocytes during the repair process, accelerating the formation and repair process of the cartilage tissue; the carboxyl groups in the oxidized chondroitin sulfate react with the amino groups in the cartilage matrix to achieve the adhesion of the hydrogel to the damaged cartilage matrix; the introduction of the boric acid group forms a borate ester bond with the hydroxyl group on the metal surface, creates an adhesion group for the surface of the hydrogel material, can provide more binding sites, increase the binding opportunities of bone cells to the surface of the hydrogel material, and achieve the technical effect of promoting cell adhesion; the surface of T-ZIF-8 after high-temperature heat treatment is negatively charged, and can react with the positively charged Ca in physiological fluids. 2+ The combination to form amorphous calcium phosphate is beneficial to further improve the cartilage repair ability of the hydrogel material. T-ZIF-8 modified with 2,4-toluene diisocyanate selectively migrates to the tendon, releasing zinc ions, improving its antibacterial and antimicrobial properties, promoting collagen secretion, and promoting tendon repair. At the same time, Mg-MOF modified with SIKVAV peptide migrates to the cartilage, releasing magnesium ions, inducing cell differentiation, and promoting cartilage regeneration. The two work synergistically to improve the cell affinity of the hydrogel material and promote bone cell regeneration.
[0117] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.
[0118] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a cartilage repair hydrogel material, characterized in that: The preparation method comprises the following steps: S1. Slice the silkworm cocoon and crush it through a 100-mesh sieve, add deionized water and mix, extract at 90-100°C for 8-10h, extract 2-3 times, combine the extracts and filter to obtain a filtrate, concentrate the filtrate by rotary evaporation at 50-60°C to 30-40% of the volume of the filtrate to obtain a concentrate, add trypsin, perform enzymolysis at 32-36°C for 3-5h to obtain an enzymolysis solution, place the enzymolysis solution in an autoclave, inactivate the enzyme in a boiling water bath for 12-16min, cool to room temperature, centrifuge at 5000-7000rpm for 8-10min, take the supernatant, pass the supernatant through a 0.22μm filter membrane, and irradiate with ultraviolet light for 20-30min to obtain a silk fibroin peptide solution for standby use; S2, dissolving the oxidized chondroitin sulfate in a phosphate buffer solution with a pH of 7.5 and a concentration of 0.01 mol / L for 1-2 hours, adding the silk fibroin peptide solution under a nitrogen atmosphere, heating to 65-75° C., stirring evenly, obtaining the silk fibroin peptide / oxidized chondroitin sulfate, and setting aside; S3, dissolving 3-aminophenylboronic acid in dimethyl sulfoxide to obtain a 3-aminophenylboronic acid solution; adding the 3-aminophenylboronic acid solution to the silk fibroin peptide / oxidized chondroitin sulfate obtained in S2 under an argon atmosphere, adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide, heating to 70-80° C., stirring at 6000-8000 rpm for 20-30 min, obtaining silk fibroin peptide / oxidized chondroitin sulfate / 3-aminophenylboronic acid, and setting aside; S4, dissolving T-ZIF-8 in a mixed solvent of dichloromethane and methanol in a volume ratio of 4:1, adding 2,4-toluene diisocyanate, stirring at 3000-5000 rpm for 2-3 hours, filtering, taking the precipitate, and drying at 80° C. for 5-6 hours to obtain 2,4-toluene diisocyanate-modified T-ZIF-8, which is set aside; S5, dissolving Mg-MOF in deionized water, adding SIKVAV peptide, magnetically stirring at 1000-2000 rpm for 10-14 h, centrifuging at 10000-15000 rpm for 8-14 min, taking the precipitate, washing it with deionized water for 2-3 times, and vacuum drying to obtain SIKVAV peptide-modified Mg-MOF for later use; S6. Add D-α-tocopherol polyethylene glycol 1000 succinate, 2,4-toluene diisocyanate-modified T-ZIF-8 and SIKVAV peptide-modified Mg-MOF to the silk fibroin peptide / oxidized chondroitin sulfate / 3-aminophenylboronic acid obtained in S3, cross-link under ultraviolet light to obtain a cartilage repair hydrogel material.
2. The method for preparing a cartilage repair hydrogel material according to claim 1, characterized in that: In S1, the material-liquid ratio of the silkworm cocoon to the ionized water is 1 g:16-20 mL; and the added amount of the trypsin is 0.4-0.8% of the mass of the silkworm cocoon.
3. The method for preparing a cartilage repair hydrogel material according to claim 2, characterized in that: In S2, the amount of the oxidized chondroitin sulfate added to the phosphate buffered saline solution is 0.3-0.5 g / mL; the mass volume ratio of the oxidized chondroitin sulfate and the silk fibroin peptide solution is 1-2 g:10-12 mL.
4. The method for preparing a cartilage repair hydrogel material according to claim 3, characterized in that: In S2, the method for preparing oxidized chondroitin sulfate specifically comprises the following steps: Dispersing chondroitin sulfate in anhydrous ethanol to obtain a chondroitin sulfate dispersion, dissolving sodium periodate in distilled water to obtain a sodium periodate aqueous solution, mixing the chondroitin sulfate dispersion and the sodium periodate aqueous solution, reacting for 3-5 hours in an ice bath in the dark, centrifuging at 2000-3000 rpm for 20-30 minutes, dialyzing for 68-74 hours using a dialysis bag with a molecular weight cutoff of 5 kD, and freeze-drying the dialyzate to obtain oxidized chondroitin sulfate; The mass volume ratio of the chondroitin sulfate to anhydrous ethanol is 10-15 g:50-60 mL; the mass volume ratio of the sodium periodate to distilled water is 5-6 g:30-50 mL.
5. The method for preparing a cartilage repair hydrogel material according to claim 4, characterized in that: In S3, the mass volume ratio of the 3-aminophenylboronic acid to dimethyl sulfoxide is 8-10 g:40-50 mL; the volume mass ratio of the 3-aminophenylboronic acid solution, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide is 10-20 mL:0.1-0.2 g:0.08-0.12 g.
6. The method for preparing a cartilage repair hydrogel material according to claim 5, characterized in that: In S4, the preparation method of T-ZIF-8 specifically comprises the following steps: Dissolve zinc nitrate hexahydrate in methanol to obtain a zinc nitrate solution, and dissolve 2-methylimidazole in methanol to obtain a 2-methylimidazole solution; disperse the zinc nitrate solution in the 2-methylimidazole solution, stir for 1-2 minutes, centrifuge at 10000-15000 rpm for 8-12 minutes, take the precipitate, wash it with methanol and deionized water 2-3 times, and vacuum dry it to obtain ZIF-8; heat treat ZIF-8 in an oxygen atmosphere at 200° C. for 4-5 hours to obtain T-ZIF-8; The amount of zinc nitrate hexahydrate dissolved in methanol is 28-32 mg / mL; the amount of 2-methylimidazole added in methanol is 30-35 mg / mL; the amount of T-ZIF-8 added in a mixed solvent of dichloromethane and methanol is 10-12 mg / mL; the mass volume ratio of T-ZIF-8 to 2,4-toluene diisocyanate is 100-120 mg:1 mL.
7. The method for preparing a cartilage repair hydrogel material according to claim 6, characterized in that: In S5, the preparation method of Mg-MOF specifically comprises the following steps: 2,5-dihydroxyterephthalic acid, Mg(NO3)2·6H2O and polyvinylpyrrolidone are added to N,N-dimethylacetamide, dispersed by ultrasonication, and ammonia water is added. The mixture is heated at 100-120°C for 8-10 hours, centrifuged at 8000-10000 rpm for 6-10 minutes, and the precipitate is taken, washed with acetone and deionized water for 2-3 times, and dried in vacuo to obtain Mg-MOF. The mass ratio of the 2,5-dihydroxyterephthalic acid, Mg(NO3)2·6H2O and polyvinyl pyrrolidone is 15-17mg:28-30mg:10-12mg; the amount of polyvinyl pyrrolidone added to N,N-dimethylacetamide is 1.5-1.7mg / mL; the volume ratio of ammonia water to N,N-dimethylacetamide is 1mL:100-120mL; the amount of Mg-MOF added to deionized water is 1-1.4mg / mL; the mass ratio of Mg-MOF to SIKVAV peptide is 100mg:1-1.2mg.
8. The method for preparing a cartilage repair hydrogel material according to claim 7, characterized in that: In S6, the volume mass ratio of the silk fibroin peptide / oxidized chondroitin sulfate / 3-aminophenylboronic acid, D-α-tocopheryl polyethylene glycol 1000 succinate, WYRGRL-modified ZIF-8 and SIKVAV-modified Mg-MOF is 100 mL: 0.01-0.05 g: 0.5-0.7 g: 0.1-0.2 g.
9. A cartilage repair hydrogel material, characterized in that: The cartilage repair hydrogel material is prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Method of chemically grafting and stabilizing biological coating macromolecules on polyester fibre surface
CN101956318A
Photo-thermal antibacterial hydrogel and preparation method thereof
CN116440317A
Step-by-step targeting micelle for treating rheumatoid arthritis as well as preparation method and application of step-by-step targeting micelle
CN117815176A
Double-targeting metal ion network hydrogel as well as preparation method and application thereof
CN117982675A
Preparation method and application of injectable nano composite hydrogel for relieving osteoarthritis
CN119258007A
Cited By
HA-PAS hydrogel for enhancing cartilage repair of early osteoarthritis and preparation method of HA-PAS hydrogel
CN121337711A